Cognitive functions in euthymic patients with bipolar disorder. - Ozdel O; Karadag F; Atesci FC; Oguzhanoglu NK; Cabuk T; Ozdel, Osman; Karadag, Filiz; Atesci, Figen C; Oguzhanoglu, Nalan Kalkan; Cabuk, Talip (Annals of Saudi Medicine)
Background: Recent studies have focused on the nature of cognitive dysfunction in bipolar patients. The purpose of the current study was to investigate cognitive performance of individuals with bipolar disorder compared to healthy control subjects during a well-established euthymic period.Methods: The sample consisted of 27 bipolar euthymic patients and 21 control subjects. Verbal and visual memory performance, attention, executive functions and psychosocial functions were evaluated for each participant.Results: Bipolar patients showed significant attentional deficit and executive dysfunction and also poor performance on verbal and visual memory tasks compared to the controls. Illness duration and lifetime total episode number and previous episode with psychotic features was associated with worsened performance on attention, executive and memory tasks. Psychosocial functioning was not associated with cognitive deficit.Conclusions: The present study showed persistent cognitive impairment on inhibitory control and selective attention as well as poor performance on verbal and visual memory tests in a group of bipolar euthymic patients. The impaired neuropsychological performance was associated with duration of illness, total number of episodes per lifetime, and previous episodes with psychotic features. Attentional dysfunction seemed to be a trait abnormality for the sample studied.